The optimal duration of capecitabine plus temozolomide in patients with well‐differentiated pancreatic NETs with or without maintenance therapy. (5th April 2022) - Gao, Heli; Dong, Jia; Zhang, Wuhu; Xu, Huaxiang; Ye, Longyun; Li, Hao; Wang, Wenquan; Liu, Liang; Yu, Xianjun
Abstract: Background: The optimal duration of capecitabine combined with temozolomide (CapTem) for metastatic pancreatic neuroendocrine tumours (PanNETs) remains controversial. The present study aimed to assess the activity and safety of prolonged CapTem and Cap maintenance therapy in patients with metastatic PanNETs. Methods: Retrospective real‐world data of 94 patients with metastatic PanNETs were obtained from one cancer centre. Fifteen patients were treated with Cap maintenance therapy after fixed 12–13 cycles of CapTem (group I), 44 patients were treated with prolonged CapTem until disease progression (group II), and 35 patients were treated with fixed 12–13 cycles of CapTem (group III). Results: The mean ± SE follow‐up period was 41.79 ± 26.31 months. The median CapTem treatment duration was 12 months in group I and 14 months in group II. The median time to best partial response was 12 months both in groups I and group II. The objective response rates of groups I and II were significantly higher than those of group III (73.3%, 41.9%, and 20%, respectively, p = .002). The median progression‐free survival (mPFS) of group I and group II was significantly higher than that of group III (35 months, 26 months vs. 19 months, p < .001). Safety analysis of the three groups indicated rare events of grade 3–4 toxicities, with nausea, vomiting, fatigue, and anaemia being the most common adverse effects. Conclusions: Patients with PanNETs who responded well to CapTem treatment may benefit from prolonged CapTem and Cap maintenance therapy after fixed cycles. Prospective studies are encouraged to further explore the prolonged CapTem treatment and maintenance therapy. Abstract : Patients with pancreatic neuroendocrine tumours (PanNETs) who responded well to capecitabine combined with temozolomide (CapTem) treatment or did not reach maximum partial response after standard cycles may benefit from prolonged CapTem and Cap maintenance therapy, which conferred longer progression‐free survival and well‐tolerated adverse events. The extended duration of CapTem treatment and maintenance therapy needs to be explored in further prospective studies.